Powerful frequencies : radio, state power, and the cold war in Angola, 1931-2002 - Moorman, Marissa Jean (New African histories series., 2019)
"Radio technology and broadcasting played a central role in the formation of colonial Portuguese Southern Africa and the postcolonial nation-state, Angola. Moorman details how settlers, the colonial state, African nationalists, and the postcolonial state all used radio to project power, while the latter employed it to challenge empire"--